Can Young Universities Achieve World-Class Status? - Salmi, Jamil (International Higher Education, 2013)
What chance does a university stand to be among the best, if it does not have hundreds of years of experience? The top 10 universities in the latest Shanghai Academic Ranking of World Universities ranking (2011) were all founded before 1900, and two are more than eight centuries old. As is the case with good wines, academic excellence requires a wealth of expertise, careful care, and a long maturity period.